On Regularized T-Matrix Formulations of Wave Scattering by Dielectric Cylinders in Planar Layered Medium - Hatipoglu, M. Enes; Alparslan, Aytac; Dikmen, Fatih (IEEE, 2024)
[No abstract available]
IEEE ITNC-USNC-URSI Radio Science Meeting / IEEE International Symposium on Antennas and Propagation (AP-S) -- JUL 14-19, 2024 -- Florence, ITALY